Extensive blooms due to Cochlodinium polykrikoides: New to Costa Rica - Vargas Montero, Maribelle (2004)
At the beginning of April of 2004 an extensive bloom produced by Cochlodinium polykrikoides was detected, embracing the whole Pacific coast of Costa Rica. The bloom was characterized by a red-oxide colour and was located in front of the beaches of Puntarenas and Caldera in the Gulf of Nicoya, Costa Rica (10°N, 85°W). This phenomenon had never observed before in this country; the species dominated other phytoplankton usually responsible for blooms. The phenomenon started during the previous dry season (from December 2003 to March 2004) showing an important increase in April.